2016
DOI: 10.1007/s00784-016-1950-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of air polishing and an amino acid buffered hypochlorite solution to dentin surfaces and periodontal ligament cell survival, attachment, and spreading

Abstract: The use of air polishing or application with Perisolv amino acid buffered hypochlorite solution was effective in treating root surfaces and allowed for near 100 % PDL cell survival, attachment, and spreading onto all root surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…An important aspect that needs to be discussed is that despite the fact that at 6 months after therapy, a dramatic reduction in the percentages of sites with PD ≥ 5 mm was measured in both groups; the magnitude of the improvement was statistically significantly higher when NaOCl gel was also applied. These clinical results appear to support the findings from "in vitro" studies which have provided evidence for the antibacterial effect of this novel NaOCl formulation and its positive effects on the survival, attachment and spreading of periodontal ligament cells [14,15].…”
Section: Discussionsupporting
confidence: 81%
“…An important aspect that needs to be discussed is that despite the fact that at 6 months after therapy, a dramatic reduction in the percentages of sites with PD ≥ 5 mm was measured in both groups; the magnitude of the improvement was statistically significantly higher when NaOCl gel was also applied. These clinical results appear to support the findings from "in vitro" studies which have provided evidence for the antibacterial effect of this novel NaOCl formulation and its positive effects on the survival, attachment and spreading of periodontal ligament cells [14,15].…”
Section: Discussionsupporting
confidence: 81%
“…An enhanced cell attachment could be also caused by erythritol. This assumption is supported by an observation, that spreading of periodontal cells on erythritol‐treated dentin was somewhat higher compared to untreated controls (Schmidlin et al., ).…”
Section: Discussionmentioning
confidence: 65%
“…These osteoconductive particles may have compensated the adverse effects of endotoxin and previous contamination. AA with erythritol also improved osteoblast‐like cell proliferation probably due to improved cell spreading . For the fibroblast cells, the one study that evaluated cell proliferation showed that cell viability on pristine samples equaled those following AA with SB.…”
Section: Discussionmentioning
confidence: 99%
“…AA with erythritol also improved osteoblast-like cell proliferation 60,84 probably due to improved cell spreading. 103 For the fibroblast cells, the one study that evaluated cell proliferation showed that cell viability on pristine samples equaled those following AA with SB. Besides the ablation potential of SB, this result can be due to the fact that this study used one bacterial species (Porphyromonas gingivalis) instead of complex biofilm.…”
Section: Contaminated Surfacesmentioning
confidence: 99%